Cutaneous Manifestations in Mastocytosis: Update - Ferreira, Sandra (2020)
Introduction: Mastocytosis is characterized by the clonal expansion of morphological and immunophenotypically abnormal mast cells in different organs. The skin is the most frequently affected tissue. Virtually all children and more than 80% of adult patients with mastocytosis show cutaneous lesions.Material and Methods: The present article describes the symptoms and signs in cutaneous mastocytosis, based on the review of recently published international consensus guidelines.Discussion: According to the 2016 World Health Organization classification, mastocytosis can be divided in cutaneous mastocytosis, systemic mastocytosis and mast cell sarcoma. Cutaneous mastocytosis is subclassified in three subtypes: maculopapular cutaneousmastocytosis, diffuse cutaneous mastocytosis and cutaneous  astocytoma. Telangiectasia macularis eruptiva perstans is no longerconsidered a distinct entity.Conclusion: Based on the age of onset, cutaneous manifestations of mastocytosis can be variable. The classification of cutaneous mastocytosis has recently been updated. Typically, in patients with childhood-onset mastocytosis, the disease occurs as cutaneous mastocytosis and shows spontaneous resolution around puberty. In contrast, adult patients, despite having also cutaneous lesions, often show systemic involvement and the course of the disease is usually chronic.